Model Learning Cycle 5E Berbantuan LKPD Berbasis Three-Dimensional Thinking Graph dan Pengaruhnya Terhadap Scientific Reasoning Pada Siswa SMP - Hamidita Putri Ristia; Ulin Nuha; Supeno Supeno (Universitas Pendidikan Mandalika, 2023)
This study aims to analyze the effect of the 5E learning cycle model assisted by LKPD based on a three-dimensional thinking graph on scientific reasoning and the improvement of scientific reasoning. The research method was a quasi-experiment using a non-equivalent control group design. The research subjects consisted of 32 students of class VII SMP. The research instruments were tests and data analysis techniques used: the normality test, the independent sample t-test, and the N-gain test. This study's results showed that the Independent Sample T-Test test obtained a significance value (2-tailed) of 0.000, which means there was a significant effect. The N-gain test results showed a value of 0.51 with moderate criteria. It showed that the 5E learning cycle model assisted by LKPD based on a three-dimensional thinking graph influences scientific reasoning which was shown by an increase in students' scientific reasoning scores.